The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5219/1763
|View full text |Cite
|
Sign up to set email alerts
|

The potential of goat meat as a nutrition source for schoolchildren

Abstract: The issue of rational nutrition of children is still extremely relevant and an effective factor in ensuring the preservation of the life and health of children. Pathological conditions associated with intolerance to certain components of food are increasingly common. Biologically complete products play an important role in the organization of rational nutrition of children, which can be created only in industrial production conditions. When assessing the chemical composition of experimental goat meat samples (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…Statistical processing was performed in Microsoft Excel 2016 in combination with XLSTAT. Values were estimated using mean and standard deviations (Tokysheva et al, 2022;Rioja-Lang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Statistical processing was performed in Microsoft Excel 2016 in combination with XLSTAT. Values were estimated using mean and standard deviations (Tokysheva et al, 2022;Rioja-Lang et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…− Sampling methods and their preparation for analysis were carried out according to GOST 13928-84 − The acidity was determined by titrimetric methods according to GOST 3624-92 − Fat determination was carried out by the methods specified in GOST 5867-90 − Determination of milk density was carried out according to GOST R54758-2011 − According to GOST 23327-98, the Kjeldahl method determined the mass fraction of the total amount of protein (GOST 3624, 1992;GOST 5867, 1990;GOST 54758. 2011, GOST 25179, 2014GOST 23327, 1998;Tokysheva et al, 2022) Tests on sheep's milk cheese were carried out in the research laboratory for assessing the quality and safety of food products at the Almaty Technological University (Almaty).…”
Section: Methodsmentioning
confidence: 99%
“…Despite the positive growth in life expectancy, it is worth noting that it does not correspond to the country's income levels. The life expectancy of the Economic Cooperation Organization countries, such as Chile and Turkey, with similar GDPs, is 80 years [3]. The analysis of food products presented on the market of our country has shown that the following areas are developing dynamically: the production of baby food products, therapeutic and preventive directions.…”
Section: Introductionmentioning
confidence: 94%